2018
DOI: 10.1021/jacs.8b01412
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared-Emitting CuInS2/ZnS Dot-in-Rod Colloidal Heteronanorods by Seeded Growth

Abstract: Synthesis protocols for anisotropic CuInX2 (X = S, Se, Te)-based heteronanocrystals (HNCs) are scarce due to the difficulty in balancing the reactivities of multiple precursors and the high solid-state diffusion rates of the cations involved in the CuInX2 lattice. In this work, we report a multistep seeded growth synthesis protocol that yields colloidal wurtzite CuInS2/ZnS dot core/rod shell HNCs with photoluminescence in the NIR (∼800 nm). The wurtzite CuInS2 NCs used as seeds are obtained by topotactic parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 57 publications
5
65
0
Order By: Relevance
“… 2 However, under seeded growth conditions, the crystal structure of the CIS seed NCs has a dramatic impact on the morphology of the product CIS/ZnS hetero-NCs, leading to CIS/ZnS dot core/rod shell heteronanorods, if wurtzite CIS NCs are used as seeds and the [ZnS] monomer concentration is allowed to build-up by delaying the injection of the seeds with respect to the injection of the Zn- and S-precursors. 78 This recent study clearly demonstrates the crucial role of the monomer formation rates in determining the outcome of shelling reactions, in agreement with the mechanism proposed above. There are also studies that used conditions that favor cation exchange (e.g., addition of only Zn-precursors), resulting in (CIS, ZnS) alloy NCs with high Zn-content and consequently very large blue-shifts (340 meV).…”
Section: Resultssupporting
confidence: 88%
“… 2 However, under seeded growth conditions, the crystal structure of the CIS seed NCs has a dramatic impact on the morphology of the product CIS/ZnS hetero-NCs, leading to CIS/ZnS dot core/rod shell heteronanorods, if wurtzite CIS NCs are used as seeds and the [ZnS] monomer concentration is allowed to build-up by delaying the injection of the seeds with respect to the injection of the Zn- and S-precursors. 78 This recent study clearly demonstrates the crucial role of the monomer formation rates in determining the outcome of shelling reactions, in agreement with the mechanism proposed above. There are also studies that used conditions that favor cation exchange (e.g., addition of only Zn-precursors), resulting in (CIS, ZnS) alloy NCs with high Zn-content and consequently very large blue-shifts (340 meV).…”
Section: Resultssupporting
confidence: 88%
“…Xia and Winckelmans were the first who have produced a CIS/ZnS dot-in-rod heterostructure via a seeded growth method [163]. WZ CIS seeds were synthesised first, that was followed by growth of ZnS tips (Figure 11).…”
Section: Synthesis Of Cu-based Multicomponent Heterostructuresmentioning
confidence: 99%
“…Scheme of the synthesis of the CIS/ZnS dot-in-rod heterostructure. Reproduced with permission from [163]. Copyright American Chemical Society, 2018.…”
Section: Figurementioning
confidence: 99%
“…Proper control over composition can lead to the formation of a different crystal structure (cubic to wurtzite structure) [28][29][30][31]. Several reports have been published on the synthesis of CIS NCs such as synthesis in solid phase [32,33], hydrothermal (including pressure cooker) [18,[34][35][36][37], decomposition of single-source precursors [28,[38][39][40][41] and the hot injection [42][43][44][45] method (Table 1). Hirpo et al [46] reported the conversion of (Ph 3 P) 2 CuIn(SEt) 4 and (Ph 3 P) 2 CuIn(SBu) 4 to CIS NCs.…”
Section: Synthetic Strategies For Cis Qdsmentioning
confidence: 99%
“…To improve the PL emission of the CIS QDs, the most common strategies employed are the coating of shells and alloying strategies [13][14][15]18,42,43,55,56,58,59,61,65,66,[68][69][70]72,74,75,78,[87][88][89][90]. Earlier studies revealed that stoichiometry control is important in obtaining highly luminescent CIS QDs [20,21].…”
Section: Tuning Of Optical Properties Of Cis Qdsmentioning
confidence: 99%